Digital Colonialism and Inequalities in Remote Higher Education of Nepal: A Critical Case Study - Thapa, Deepak; Bohara, Nirajan (International Research Journal of MMC, 2026)
The digital integration has rapidly been transforming higher education landscape in the age of artificial intelligence (AI). Guided from decolonial perspective, this study aims to explore the relevance of integrating digital tools in transforming remote higher education landscape, utilizing critical case study method. This study is grounded on qualitative research design. For this, we gathered empirical data using semi-structured interview questions from purposively selected fifteen research participants. The participants consisted of five university teachers and ten undergraduate students from three different remote higher education institutions of Kalikot district of Nepal. The data were then analyzed following Miles and Huberman’s qualitative data abstraction method of thematic analysis which included data reduction (coding), data display (categorizing) and drawing conclusion (concept/theme development). The study revealed that although digitalization plays the transformative role in shaping higher education, it is unintentionally widening the structural inequalities and perpetuating digital colonialism in remote higher education. The findings are critical as they showcase exact realties of digital transformation in remote regions and give a way forward to the government authorities and policy makers to adopt equity-based digital strategies to enhance access, quality and inclusivity in Nepal’s higher education landscape. Furthermore, the study offered some alternatives digital strategies such as Delayed tolerant Network (DTN), voice-based mobile telephony and local community radio to bridge the disparities and enhance teaching and learning.